ngoccngocc

Giúp tớ zớiiiiiiloading...

1: Thay x=49 vào A, ta được:

\(A=\dfrac{49+7}{7-3}=\dfrac{56}{4}=14\)

2: \(B=\dfrac{\sqrt{x}}{\sqrt{x}-3}+\dfrac{6\sqrt{x}}{9-x}-\dfrac{3}{\sqrt{x}+3}\)

\(=\dfrac{\sqrt{x}}{\sqrt{x}-3}-\dfrac{6\sqrt{x}}{\left(\sqrt{x}-3\right)\left(\sqrt{x}+3\right)}-\dfrac{3}{\sqrt{x}+3}\)

\(=\dfrac{\sqrt{x}\left(\sqrt{x}+3\right)-6\sqrt{x}-3\left(\sqrt{x}-3\right)}{\left(\sqrt{x}-3\right)\left(\sqrt{x}+3\right)}\)

\(=\dfrac{x-3\sqrt{x}-3\sqrt{x}+9}{\left(\sqrt{x}-3\right)\left(\sqrt{x}+3\right)}=\dfrac{\left(\sqrt{x}-3\right)^2}{\left(\sqrt{x}-3\right)\left(\sqrt{x}+3\right)}=\dfrac{\sqrt{x}-3}{\sqrt{x}+3}\)

3: \(M=A\cdot B=\dfrac{x+7}{\sqrt{x}-3}\cdot\dfrac{\sqrt{x}-3}{\sqrt{x}+3}=\dfrac{x+7}{\sqrt{x}+3}\)

\(=\dfrac{x-9+16}{\sqrt{x}+3}=\sqrt{x}-3+\dfrac{16}{\sqrt{x}+3}\)

\(=\sqrt{x}+3+\dfrac{16}{\sqrt{x}+3}-6>=2\cdot\sqrt{\left(\sqrt{x}+3\right)\cdot\dfrac{16}{\sqrt{x}+3}}-6=2\cdot4-6=2\)

Dấu '=' xảy ra khi \(\sqrt{x}+3=4\)

=>x=1(nhận)

Bình luận (0)

Các câu hỏi tương tự
Thaor
Xem chi tiết
Tớ Là Hân
Xem chi tiết
Tâm Hữu
Xem chi tiết
Tớ Là Hân
Xem chi tiết
hoang gia kieu
Xem chi tiết
Thùy Linh Bùi
Xem chi tiết
Tớ Là Hân
Xem chi tiết
Tớ Là Hân
Xem chi tiết
Tớ Là Hân
Xem chi tiết
Diệu Anh
Xem chi tiết